2011
DOI: 10.1155/2011/979214
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Body Radiosurgery for Spinal Metastatic Disease: An Evidence-Based Review

Abstract: Spinal metastasis is a problem that afflicts many cancer patients. Traditionally, conventional fractionated radiation therapy and/or surgery have been the most common approaches for managing such patients. Through technical advances in radiotherapy, high dose radiation with extremely steep drop off can now be delivered to a limited target volume along the spine under image-guidance with very high precision. This procedure, known as stereotactic body radiosurgery, provides a technique to rapidly treat selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 61 publications
(58 reference statements)
2
44
0
1
Order By: Relevance
“…A recent pooled analysis of published series using both single fraction at various dose levels and multi-fraction regimens (up to 5 sessions) entailed 1775 lesions in 1388 patients. 19 Followup was mostly short-termed (<18 months in 12/15 studies) yielding an overall local control rate of 90% and a risk of radiation myelopathy of 0.4%, with no apparent differences in early outcomes between single dose and 3-5 fraction of SBRT. Prospective randomized trials are few and largely still underway.…”
Section: Rationale Of Single Dose Versus Hypofractionated Regimensmentioning
confidence: 99%
“…A recent pooled analysis of published series using both single fraction at various dose levels and multi-fraction regimens (up to 5 sessions) entailed 1775 lesions in 1388 patients. 19 Followup was mostly short-termed (<18 months in 12/15 studies) yielding an overall local control rate of 90% and a risk of radiation myelopathy of 0.4%, with no apparent differences in early outcomes between single dose and 3-5 fraction of SBRT. Prospective randomized trials are few and largely still underway.…”
Section: Rationale Of Single Dose Versus Hypofractionated Regimensmentioning
confidence: 99%
“…This allows the system to automatically compare this marker information with reference information to move the treatment couch to the desired position [20]. Gill et al commenting on local control and toxicity of SBRT of single vertebrae spinal tumors reported that a doses of [30][31][32][33][34][35] Gy were given via Cyberknife technology, and at 34 months median follow-up (IQR, 25-40 months) for surviving patients, the 1-and 2-year Kaplan-Meier local control estimates were 80 and 73%, respectively [21]. In effect, SBRT for primary or metastatic spinal column cancers is a noninvasive procedure with excellent control rates that is being widely adopted by radiation oncologists across the United States.…”
Section: Sbrt For Spinal Column Tumorsmentioning
confidence: 99%
“…Also, when the number of beams used is sufficiently high, the choice of beam direction becomes less significant [2]. Recent developments in volumetric modulated arc techniques have the potential to create conformal dose distributions, achieve the required level of normal tissue sparing, and reduce treatment times, as compared to their static field counterparts [33].…”
Section: Planning and Procedures Effective Radiation Gy Imaging And mentioning
confidence: 99%
See 1 more Smart Citation
“…In neurooncology, spinal metastases are of major interest. A current evidence-based review of Hall et al reviewed 1388 patients with 1775 lesions treated with stereotactic body radiosurgery [19]. Over 50% of these patients received radiosurgery as a second course of radiotherapy.…”
Section: Spinal Metastasis and Primary Tumors Of The Spinementioning
confidence: 99%